Análise da educação escolar sob a ótica bourdieusiana - Dias, Robinson Alves [UNESP]; Reina, Fábio Tadeu [UNESP]; Romanatto, Maria José [UNESP]; Bedin, Regina Celia [UNESP] (My University, 2013)
There are several possibilities to understand the importance of school education, so this literature review article is to show through the sociological theory of Pierre Bourdieu that the school is not defined as a social concept of equalization, but a collaboration for the reproduction of structural society. And to be consistent with this action, the school tends to emphasize the hegemonic concepts, so that acts consciously or unconsciously on the aggregation of cultural heritage, imposed by the ruling class, ie, the layers of the corporate elite.

Várias são as possibilidades de entender a importância da educação escolar, portanto, este artigo de revisão bibliográfica vem mostrar por meio da teoria sociológica de Pierre Bourdieu que a escola não é definida como um conceito de equalização social, mas uma colaboração para a reprodução estruturante da sociedade. E ao coadunar com esta ação, a escola tende a valorizar os conceitos hegemônicos, de tal maneira que age de forma consciente ou inconsciente na agregação de valores da herança cultural, imposta pela classe dominante, ou seja, das camadas da elite societária.
Analysis of school education on the perspective of bourdieu
Keywords: School Education; Social equalization; Company; Cultural Heritage; Educação Escolar; Equalização social; Sociedade; Herança Cultural